(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
In this article, problems and solutions to the development of the principles of fine art, pencil drawing, painting composition, historical and modern aesthetic, philosophical and artistic ideas, modern realism, and modernism. To further develop our spiritual life in the future, several important things, including increasing the culture of reading books, improving the culture and art sphere, developing a creative school named after our great artists in the regions, the history of new art of Uzbekistan, modern visual arts art modern teaching culture art scientific-practical research. Academicians of the Creative Union of Art Academicians of the XXI century discussed creativity, individual artistic work, scientific art science, modern pedagogical technology, theoretical research methodology, and practical and theoretical methodology.